Synthesis, α-glucosidase inhibitory and molecular docking studies of prenylated and geranylated flavones, isoflavones and chalcones. Issue 20 (15th October 2015) - Sun, Hua; Li, Yashan; Zhang, Xiaoting; Lei, Yanan; Ding, Weina; Zhao, Xue; Wang, Haomeng; Song, Xiaotong; Yao, Qingwei; Zhang, Yongmin; Ma, Ying; Wang, Runling; et al.
Graphical abstract